Analisis Self-Adaptation Pada Perguruan Tinggi Oleh Mahasiswa Baru - Diah Sari; Dina Hermina (Jurnal Riset Multidisiplin Edukasi, 2025)
This study analyzes the self-adaptation process of college freshmen with the aim of understanding the factors that influence their adaptability. The transition from high school to college involves significant academic, social, and emotional challenges. The research method used is Systematic Literature Review (SLR), which identifies and synthesizes literature related to this topic. The results showed that freshmen adaptation includes academic, social, emotional, and institutional attachment aspects. Internal factors such as personality and motivation and external factors such as social support play an important role in the adaptation process. The findings emphasize the need for institutional support in helping freshmen face transitional challenges to improve their academic success and mental well-being.